Development of algorithm for determination of location of cable line damage using its amplitude-phase coordinate characteristics - A. V. Logunov; Yu. K. Shlyk (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. The task of prompt and accurate determination of the fault location in cable transmission lines is one of the key in the process of ensuring a reliable and uninterrupted supply of electricity to consumers. The development of a new algorithm for solving this problem, which will minimize the time and resources spent on finding damage, is an urgent area of modern research. THE PURPOSE. Consider the main shortcomings and limitations of the existing methods of determining fault location to cable lines. Develop an algorithm for the determining fault location to cable line based on the theory of long lines using the original amplitude-phase coordinate characteristics. Implement an algorithm for obtaining theoretical characteristics of the dependence of the input current parameters on the line fault coordinate using a specific numerical example. METHODS. When solving the tasks set, the methods of the theory of long lines and the classical theory of electrical circuits were used, implemented by means of the Wolfram Mathematica software package. RESULTS. The article describes the relevance of the topic, considers the main shortcomings of the existing methods of determining fault location to cable lines. An algorithm for determining the fault location for a single-phase cable line has been developed and implemented on a specific numerical example, based on the joint use of a special type of duplicated coordinate-dependent (ACC) and (FCC) characteristics calculated using the Wolfram Mathematica software package. The corresponding graphic constructions are given and a variant of the practical implementation of the proposed algorithm is described. CONCLUSION. According to the results of theoretical calculations, the proposed algorithm for determining the location of damage to a single-phase cable power transmission line allows, with a given accuracy, to determine the coordinate of damage for cases of breakage and short circuit in the entire range of line length. The obtained theoretical calculations need appropriate experimental testing in the next stage of research.